Diffuse alveolar haemorrhage secondary to e-cigarette "vaping" associated lung injury (EVALI) in a young European consumer. Issue 1 (16th July 2020) - Villeneuve, Thomas; Prevot, Grégoire; Le Borgne, Aurélie; Colombat, Magali; Collot, Samia; Ruiz, Stephanie; Lanot, Thomas; Brouchet, Laurent; Rabeau, Audrey; Noel-Savina, Elise; Didier, Alain
We report the case of a 28-year-old woman admitted with acute respiratory failure. The patient had no personal or familial medical history involving respiratory disease such as asthma, thrombotic events or bleeding. She was a heavy smoker (15 cigarettes per day for the past 5 years) and "vaped" electronic cigarettes (e-cigarettes) for 1 month prior to the incident. She consumed 10 mL of e-liquid bottled with nicotine salt (12 mg·mL −1 ) in 2 days. No cannabidiol (CBD) or tetrahydrocannabinol (THC) was detected. No other home-made components were added. The patient did not take any regular medicines or contraceptives. No consumption of cannabis, cocaine or any other drugs was reported (confirmed with negative urinary drug test). She had not travelled outside of France. She was referred to the emergency department (ED) for tachypnoea (respiratory rate 22–25 per min), desaturation at 80% in the context of dyspnoea evolving for 15 days. No cough, haemoptysis or extra-thoracic manifestations were reported. Her temperature was 36.8°C, pulse 98 beats per minute, blood pressure 123/79 mmHg. Heart sounds were regular but crackles were audible on thoracic auscultation. An alveolar and interstitial syndrome was observed on chest radiography (data not shown). Ceftriaxone and spiramycin was initiated in ED and oxygen therapy was started at 12 L·min −1 . A notable case of EVALI not involving cannabis derivatives in a 28-year-old woman who developed an intra-alveolar haemorrhage without differential diagnosis after surgical lung biopsy and requiring extracorporeal membrane oxygenation http://bit.ly/2TXx79K